Blackness or incipient blackness? Metaphors of the mulato in two poems by Nicolas Guillén - Díaz Atilano, Carmen Jhoana (2024)
This work supports as a hypothesis that, in the poems of Sóngoro cosongo by Nicolás Guillén, what we call an “incipient blackness” is appreciated. This manifests itself in advance, since the collection of poems that we are going to analyze dates back to 1931, while the term négritude (a word taken from French) was only coined in 1935 by the black French communist writer, poet and politician Aimé Césaire, in his collection of poems Notebook of a return to the native country and in the pages of his magazine L’étudiant noir. The latter understood blackness as a concept of anti-colonial protest, which implied the revaluation of black origin and African cultural values. It was not only about highlighting its authenticity, but about taking a stand in favor of the oppressed. For this reason, we believe that Guillén places mulatto in an intermediate position between Western and black, but showing greater identification with African roots.